Corruption in business: motives and influence on shadow economy - Momot, Tetiana; Chekh, Nataliia; Prylypko, Sergii; Filonych, Olena; Cherednychenko, Oleksandr (Business: Theory and Practice, 2023)
The paper devoted to the research of the corruption offenses in the activity of business entities which are quite a common phenomenon that causes serious moral, economic and political problems, hinders development and distorts fair competition. The purpose of the study is to reveal the distinguishing peculiarities of corruption in business to business relations and special features of the behavior of the corrupt company employee in the context of corruption influence on the level of the shadow economy of Ukraine. The differences between employment in the public and private sectors are highlighted. Analyzing relevant literature, the paper offers a model of corruption-related decision-making of an enterprise employee that takes into account all the factors that may influence a choice of involvement in the corruption offenses. The main causes of corruption in business are viewed as the competitive advantages the company can gain and the level of corruption around it. The research proves that the company can start participating in corrupt practices because many representatives of the business environment are involved in it, claiming that it is the only way to survive. The paper proves the impact of corruption on the level of shadow economy on the example of Ukraine. The essence and constituent elements of the shadow economy are revealed, as well as the negative consequences of the shadow economy, the spread of which is facilitated by corruption in the authorities and government. We proved that the higher level of corruption in the public sphere will result in a higher level of corruption inside the business environment. We proved that special attention should be given to the corruption in business relations as a sub-set of a general corruption phenomenon. The suggested by authors model of corruption-related decision making in business to business relations facilitates better understanding of the true nature of the business corruption phenomenon and development of well thought anti-corruption measures both on company and government levels.